How is

(1!*4!) + ((2!-1!)*3!) + ((3!-2!-1!)*2!) + ((4!-3!-2!-1!)*1!) = 24 + 6 + 6 + 13 ?

((4!-3!-2!-1!)*1!) = 24 - 6 - 2 - 1 = 15 therefore it should be 24 + 6 + 6 + 15 = 51.

Similarly, how is

1!*5! + (2!-1!)*4! + (3!-2!-1!)*3! + (4!-3!-2!-1!)*2! + (5!-4!-3!-2!-1!)*1!

= 120 + 24 + 18 + 26 + 71 = 259 ?

(4!-3!-2!-1!)*2! = (24 - 6 - 2 - 1)*2 = 15*2 =30

Similarly (5!-4!-3!-2!-1!)*1! = 120 - 24 - 6 - 2 - 1 = 87

Therefore it should be 120 + 24 + 18 + 30 + 87 = 279.

Is there something I am missing here? I checked it o...